Focusing on Consumer Behavior: Factors Influencing Hotel Choice: A Study of Price, Service Quality, and Electronic Word of Mouth (EWoM) in Bantul, Yogyakarta - Maarif, Samsul; Widarta, Widarta (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the effect of price, service quality, and electronic word of mouth on the decision to choose a hotel in Bantul Yogyakarta. The research data were obtained from distributing questionnaires to the object of research. The sampling technique used is non probability sampling, using purposive sampling method. The type of research used in this research is quantitative. The sample used in this study were customers who had chosen to stay at hotels in the Bantul Yogyakarta area as many as 97 respondents. The results of this study indicate that price has a positive and significant effect on decisions to choose, service quality has a positive and significant effect on decisions to choose, electronic word of mouth has a positive and significant effect on decisions to choose, simultaneously price, service quality, and electronic word of mouth have a positive and significant effect on decisions to choose.